A class of second order BVPs on infinite intervals - Smail Djebali (Electronic Journal of Qualitative Theory of Differential Equations, 2006)
In this work, we are concerned with a boundary value problem associated with a generalized Fisher-like equation. This equation involves an eigenvalue and a parameter which may be viewed as a wave speed. According to the behavior of the nonlinear source term, existence results of bounded solutions, positive solutions, classical as well as weak solutions are provided. We mainly use fixed point arguments.